Tourism development principles and practices - Stanley, Alexander (Wilmington, De Kaufman Press, 2023)
"This book is written in a simple and in plain language with introduction to tourism that assumes no prior knowledge of what tourism is and how it affects our everyday life." --
Introduction -- Developments of tourism in 21st century -- Tourism and economic development -- Consumer motivations in tourism industry -- Challenges and opportunities for sustainable tourism development -- Tourism marketing management -- Environmental management of tourism development -- Third world critique of tourism in new development
Reprint, 2023.
Includes bibliographical references and index.
Keywords: Tourism -- Development; Tourism -- Management